Domenico Pastore, Dalla superficie al volume. Una lettura grafica dei Solidi di Cesare Leonardi, Libria, Melfi 2021 (diségno, 2022)
The study settled by Domenico Pastore in his book Dalla superficie al volume. Una lettura grafica dei Solidi di Cesare Leonardi, was conducted with the aim of promoting the knowledge of one of the key figures of Italian design: Cesare Leonardi. At the beginning of the 1980s, Leonardi focused on recycling and recovery operations of multilayer wood panels, used for the formwork of reinforced concrete structures, as a material for the construction of a variety of objects for domestic use. Leonardi anticipates –as Pastore observes in the introduction– some current themes of contemporary research based on the reuse of materials and on an artisan/authorial approach to reflection on the design project, also in terms of feasibility. [read more]